Mapping Human Capital, Social Capital, and Well Being in Informal Self Employment: A Bibliometric Study - Ni Luh Putu Sariani; Setyo Riyanto; Lenny Christina Nawangsari; Kasmir (Economics and Business Journal (ECBIS), 2026)
This study aims to map the development of scientific research on human capital, social capital, and the well-being of self-employed workers in the informal sector during the period 2015–2025. Employing a bibliometric approach based on Scopus data, this study analyses 102 scientific documents through indicators of annual publication output, country contribution, institutional affiliation, citation level, co-authorship collaboration networks, and keyword co-occurrence using VOSviewer software. The analysis reveals a significantly upward publication trend, particularly in 2024 and 2025. China, the United Kingdom, and Indonesia are recorded as the countries with the highest publication contributions. The most cited article is the work of Prasetyo & Kistanti (2020), which comprehensively integrates human capital, social capital, and entrepreneurship as pillars of sustainable economic growth. Co-authorship network analysis indicates fragmented collaboration patterns, while keyword co-occurrence mapping identifies four main thematic clusters: (1) well-being and entrepreneurship; (2) social capital and human capital; (3) livelihood and the informal sector; and (4) knowledge and sustainable development. These findings suggest the need to strengthen cross-country research collaboration and to expand inquiry into the interaction between human capital and social capital in enhancing the well-being of self-employed workers in the informal sector, particularly in developing countries. This study contributes to the literature by providing an integrated bibliometric overview of how human capital and social capital are positioned in relation to the well-being of self-employed workers in the informal sector